CHARACTERIZATION OF QUALITY ATTRIBUTES OF MANGO CV. ’ATAULFO’ AT DIFFERENT MATURITY STAGES - COSTA, MARYLIA DE SOUSA; ALMEIDA, FRANCISCO DE ASSIS CARDOSO; COSTA, JOSENARA DAIANE DE SOUZA; FIGUEIREDO NETO, ACÁCIO; GOMES, JOSIVANDA PALMEIRA (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2021)
The objective of this study was to evaluate the specific characteristics of three maturation of the ’Ataulfo’ mango, as well as the correlation of a non-destructive method as the DA Meter Absorption Difference Index (Turoni), with destructive physical-chemical parameters. The mangoes were harvested at stages 2, 3 and 4, the following variables were determined: loss of mass, length, diameter, shell and pulp color and their coordinates L * a * b *, firmness, DA Index, yield, pH, soluble solids, titratable acidity and vitamin C. The experimental design was completely randomized with ten repetitions. The results were submitted to the test of means and simple correlation. Physical and physico-chemical analyzes such as mass, length, pulp yield, can be used as a basis for determining maturation stages, but the DA Index differentiation of fruits in different maturation classes, in addition to having a good correlation with firmness, SST, ATT and pH, with high coefficients, -0.92, 0.94, 0.97 and -0.93, respectively. Thus, the determination of this index represents a potential tool based on non-destructive analysis to determine the maturation of ’Ataulfo’ varieties.